Studies on Schismatoglottideae of Borneo LXVIII : two new species of Schismatoglottis endemic to the Danum Valley Conservation Area, Sabah, Malaysian Borneo - Wong, Sin Yeng; Boyce., Peter C; Kartini, Saibeh (Taylor & Francis, 2019)
Schismatoglottis clivemarshii and Schismatoglottis priapica are described and illustrated as new species from the Danum Valley Conservation Area, Tawau, Lahad Datu, Sabah, to where both are endemic.